A study on academic achievement motivation and academic achievement of the class X students of Dibrugarh district, Assam - Kataky, Bilina Devi; Chaliha, Asomi (Edelweiss Applied Science and Technology, 2024)
The pursuit of academic achievement is an important feature of educational endeavours worldwide, serving as a crucial marker of success and progress for students, educators, and society at large. The problem addressed by the study on Academic Achievement Motivation and Academic Achievement of the Class X Students of Dibrugarh District, Assam lies in the need to comprehensively understand the factors influencing academic performance in this specific demographic context. The study explores academic achievement motivation and academic achievement of the class X students of Dibrugarh District, Assam and compares it on the grounds of gender differences. It helps to prevent a serious breakdown in the personal and educational life of students. The research focuses on the Class X students of the Dibrugarh District, Assam and examines gender differences in academic achievement motivation and academic achievement. The study utilizes a method of descriptive research and Academic Achievement Motivation Test (1984) developed by Dr.T. R Sharma to gather data from the 386 class X Dibrugarh District students which were selected by multiphase sampling method to measure their Academic Achievement Motivation. The student's academic achievement is determined by their percentage of marks in the class IX board examination. To find out more about the relationship between academic achievement motivation and academic achievement, statistical analysis is used, particularly product moment coefficient of correlation. These results highlight the significance of identifying and encouraging students' motivation for academic achievement. The future scope for several avenues of research and practical interventions to further enhance understanding and address the complex dynamics of academic achievement motivation and academic performance among Dibrugarh district, Assam Class X students.